Partnership of Midwife and Traditional Birth Attendants in Aid Delivery at Sub District Singkil District Aceh Singkil - Hayati, Mustika; Harbiyah, Harbiyah; Agustina, Agustina (Universitas Ubudiyah Indonesia, 2018)
The traditional birth attendants and midwife partnership in Singkil sub-district has been running but there are still non-partnering traditional birth and the proportion of deliveries delivered by traditional birth is still high at 10%. It can be reviewed about the process of building partnership of traditional birth and midwife in delivery aid to know barrier in the implementation of partnership of traditional birth and midwife in delivery aid in Singkil sub-district of Aceh Singkil Regency. This research uses qualitative design with grounded theory approach. This research was conducted in 1 Sub-District consists of 6 Villages, DesaSukaDamai, PayaBumbu, Teluk Ambon, PakalPasir, DesaPemuka and TelukRumbia. The respondents in this study were traditional birth partners, non-partnering traditional birth, midwifes, KIA program holders, religious figures, public figures, postpartum assisted by traditional birth partners during this research period, postpartum mothers who were assisted by traditional birth did not partners during the study period and postpartum family. The result of the research shows that the obstacles in the implementation of the traditional birth and midwife partnership program in the aspect of the allocation of special funds for this program are not sufficient, facilities and infrastructure are inadequate, the means of transportation for health access is not available, there are still traditional birth who do not want to partner with the reason of financial results which they get is not appropriate and age factors are old, and there are still pregnant women who do not want to give birth in health facilities on the grounds of remote, difficult transportation access and feel comfortable with traditional birth. Traditional birth do not feel to have an advantage in the economic aspect but have an advantage in aspect of midwifery science. In contrast, midwifes felt that the partnership program provided benefits to facilitate the work of the village midwife. For pregnant women this partnership gives a positive meaning because pregnant women feel calm and comfortable because the childbirth is assisted by traditional birth and midwife. For village midwifes and program holders to maintain good relation relationships with traditional birth who partner and arrange regular meetings for effective communication. Invite traditional birth who have not partnered by involving them as posyandu cadres and provide health education to the community about the benefits of deliveries in health facilities.Keywords: midwife, patnershipdan aid delivery, traditional birth